Fire Arm Injury & Homicidal Deaths Presenting at Tertiary Care Hospital of Sindh - Waheed Ali Nahyoon, Mir Khuda Bux Talpur, Ghulam Sarwar Pirzada, Afzal Memon, (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2015)
Objective: To study fire arm injury, homicidal deaths, causes and outcome at a tertiary care hospital. Study Design: Observational study. Place and Duration: January 2011 to February 2013. Material and Methods: 235 cases of violent injury including fire arm injury were studied. A detailed autopsy was conducted according to Robert Virchow`s technique in case of dead bodies. Findings were collected in a pre-designed proforma. All the biodata were noted as per medico-legal point of view. Data was entered on SPSS version 21.0 (IBM, USA). Continuous and categorical variables were analyzed using student t test and Chi square test. Microsoft excel was also used for graphing. Results: Of 235, 15.7% (n=37) were female and 84.2% (n=198) male (p=0.0001). Male to female ratio was found 5.3:1. Mean ±SD of age was noted as 39.1±11.9 years. Of 235, in 199 (84.6%) cases were of fire arm injury. Common cause of fire arm injury was quarrel (39.1%) followed by robbery (21.1%) and accidental (17.5%). Of 199 fire arm injuries, 67 were received as “dead bodies”, fifty seven died at emergency unit and remaining survived but with physical disabilities. Of 36 cases of other causes were poisoning and blunt trauma and were dead before reaching hospital. Conclusion: Very high rate of homicide with fire arm weapons was observed. Social conflict, robbery and accidental fire arm injury were most frequent.